Vasodilatory effect of formaldehyde via the NO/cGMP pathway and the regulation of expression of KATP, BKCa and L-type Ca2+ channels. (15th September 2019) - Zhao, Yun; Ge, Jing; Li, Xiaoxiao; Guo, Qing; Zhu, Yuqing; Song, Jing; Zhang, Luoping; Ding, Shumao; Yang, Xu; Li, Rui
Graphical abstract: Highlights: Vasorelaxant effect of formaldehyde (FA) on rat aortic rings was revealed. FA exposure leads to damaging effects on the rat aortas. The comparison between FA and H2 S-induced vasorelaxation has been conducted. KATP channel is revealed to be upregulated by FA when inducing vasorelaxation. Abstract: Formaldehyde (FA), a well-known toxic gas molecule similar to nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H2 S), is widely produced endogenously via numerous biochemical pathways, and has a number of physiological roles in the biosystem. We attempted to investigate the vasorelaxant effects of FA and their underlying mechanisms. We found that FA induced vasorelaxant effects on rat aortic rings in a concentration-dependent manner. The NO/cyclic guanosine 5′ monophosphate (cGMP) pathway was up-regulated when the rat aortas were treated with FA. The expression of large-conductance Ca 2+ -activated K + (BKCa ) channel subunits α and β of the rat aortas was increased by FA. Similarly, the levels of ATP-sensitive K + (KATP ) channel subunits Kir 6.1 and Kir 6.2 were also up-regulated when the rat aortas were incubated with FA. In contrast, levels of the L-type Ca 2+ channel (LTCC) subunits, Cav 1.2 and Cav 1.3, decreased dramatically with increasing concentrations of FA. We demonstrated that the regulation of FA on vascular contractility may be via the up-regulation of the NO/cGMP pathway and the modulation of ion channels, including the upregulated expression of the KATP and BKCa channels and the inhibited expression of LTCCs. Further study is needed to explore the in-depth mechanisms of FA induced vasorelaxation.